From Swiss-cheese to discrete ferroelectric composites: assessing the ferroelectric butterfly shape in polarization loops - Myroshnychenko, Viktor; Mulavarickal Jose, Pious Mathews; Farheen, Henna; Ejaz, Shafaq; Brosseau, Christian; Förstner, Jens (Physica Scripta)
We explore the polarization hysteretic behaviour and field-dependent permittivity of ferroelectric-dielectric 2D materials formed by random dispersions of low permittivity inclusions in a ferroelectric matrix, using finite element simulations. We show how the degree of impenetrability of dielectric inclusions plays a substantial role in controlling the coercive field, remnant and saturation polarizations of the homogenized materials. The results highlight the significance of the degree of impenetrability of inclusion in tuning the effective polarization properties of such ferroelectric composites: coercive field drops significantly as percolation threshold is attained and remnant polarization decreases faster than a linear decay.
Keywords: tet_topic_ferro

Time and Space Optimized Storage-based BIST under Multiple Voltages and Variations - Jafarzadeh, Hanieh; Klemme, Florian; Amrouch, Hussam; Hellebrand, Sybille; Wunderlich, Hans-Joachim (European Test Symposium, The Hague, Netherlands, May 20-24, 2024)

Vmin Testing under Variations: Defect vs. Fault Coverage - Jafarzadeh, Hanieh; Klemme, Florian; Amrouch, Hussam; Hellebrand, Sybille; Wunderlich, Hans-Joachim (IEEE Latin American Test Symposium (LATS), Maceió, Brazil, April 9-12, 2024)

Functional Safety and Reliability of Interconnects throughout the Silicon Life Cycle - Hellebrand, Sybille; Sadeghi-Kohan, Somayeh; Wunderlich, Hans-Joachim (International Symposium of EDA (ISEDA), Xi'an, China, May 10-13, 2024)

Robust Test of Small Delay Faults under PVT-Variations - Wunderlich, Hans-Joachim; Jafarzadeh, Hanieh; Hellebrand, Sybille (International Symposium of EDA (ISEDA), Xi’an, China, May 10-13, 2024)

Modeling Crosstalk-induced Interconnect Delay with Polynomial Regression - Stiballe, Alisa; Reimer, Jan Dennis; Sadeghi-Kohan, Somayeh; Hellebrand, Sybille

TS-SEP: Joint Diarization and Separation Conditioned on Estimated Speaker Embeddings - Boeddeker, Christoph; Subramanian, Aswin Shanmugam; Wichern, Gordon; Haeb-Umbach, Reinhold; Le Roux, Jonathan (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Keywords: Electrical and Electronic Engineering; Acoustics and Ultrasonics; Computer Science (miscellaneous); Computational Mathematics

Optimization of the Downlink Spectral- and Energy-Efficiency of RIS-aided Multi-user URLLC MIMO Systems - Soleymani, Mohammad; Santamaria, Ignacio; Jorswieck, Eduard; Schober, Robert; Hanzo, Lajos (arXiv:2402.16434)
Modern wireless communication systems are expected to provide improved latency and reliability. To meet these expectations, a short packet length is needed, which makes the first-order Shannon rate an inaccurate performance metric for such communication systems. A more accurate approximation of the achievable rates of finite-block-length (FBL) coding regimes is known as the normal approximation (NA). It is therefore of substantial interest to study the optimization of the FBL rate in multi-user multiple-input multiple-output (MIMO) systems, in which each user may transmit and/or receive multiple data streams. Hence, we formulate a general optimization problem for improving the spectral and energy efficiency of multi-user MIMO-aided ultra-reliable low-latency communication (URLLC) systems, which are assisted by reconfigurable intelligent surfaces (RISs). We show that a RIS is capable of substantially improving the performance of multi-user MIMO-aided URLLC systems. Moreover, the benefits of RIS increase as the packet length and/or the tolerable bit error rate are reduced. This reveals that RISs can be even more beneficial in URLLC systems for improving the FBL rates than in conventional systems approaching Shannon rates.

Maximization of Minimum Rate in MIMO OFDM RIS-Assisted Broadcast Channels - Soleymani, Mohammad; Santamaria, Ignacio; Sezgin, Aydin; Jorswieck, Eduard (2023 IEEE 9th International Workshop on Computational Advances in Multi-Sensor Adaptive Processing (CAMSAP))

NOMA-Based Improper Signaling for MIMO STAR-RIS-Assisted Broadcast Channels with Hardware Impairments - Soleymani, Mohammad; Santamaria, Ignacio; Jorswieck, Eduard (GLOBECOM 2023 - 2023 IEEE Global Communications Conference)

Insights and Challenges of Co-Simulation-based Optimal Pulse Pattern Evaluation for Electric Drives - Hölsch, Lukas; Brosch, Anian; Steckel, Richard; Braun, Tristan; Wendel, Sebastian; Böcker, Joachim; Wallscheid, Oliver (IEEE Transactions on Energy Conversion)
Keywords: Electrical and Electronic Engineering; Energy Engineering and Power Technology

Rademacher Complexity Regularization for Correlation-Based Multiview Representation Learning - Kuschel, Maurice; Hasija, Tanuj; Marrinan, Timothy (ICASSP 2024 - 2024 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

pyfds 0.3.1 - modular field simulation tool - Claes, Leander; Webersen, Manuel

Implementation of Different Communication Structures for a Rocket Chip Based RISC-V Grid of Processing Cells - Luchterhandt, Lars; Nellius, Tom; Beck, Robert; Dömer, Rainer; Kneuper, Pascal; Müller, Wolfgang; Sadiye, Babak (MBMV 2024 - 27. Workshop Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen“)
RISC-V has received worldwide acceptance in the industry and by the academic community. As of today, multiple RISC-V applications and variants are under investigation for embedded IoT systems, from resource-limited single-core processors up to multi-core systems for High-Performance Computing (HPC). Recently, the Grid of Processing Cells (GPC) platform has been proposed as a scalable parallel grid-oriented network of processor cores with local memories. This paper describes a prototype design of the GPC platform for hardware implementation at Register-Transfer Level (RTL) based on modified RISC-V Rocket processors with scratchpad memories. It introduces a scalable Chisel-based implementation of the modified Rocket cores with RTL generation and a functional test using Verilator simulation. This work also includes the adaptation of the Chipyard software toolchain to extend the compiler to multi-core grids with different local address spaces.

A Scalable RISC-V Hardware Platform for Intelligent Sensor Processing - Palomero Bernardo, Paul; Schmid, Patrick; Bringmann, Oliver; Iftekhar, Mohammed; Sadiye, Babak; Müller, Wolfgang; Koch, Andreas; Jentsch, Eyck; Sauer, Axel; Feldner, Ingo; Ecker, Wolfgang (DATE 24 - Design Automation and Test in Europe)

Geodesic Interpolation of Frame-Wise Speaker Embeddings for the Diarization of Meeting Scenarios - Cord-Landwehr, Tobias; Boeddeker, Christoph; Zorilă, Cătălin; Doddipatla, Rama; Haeb-Umbach, Reinhold (ICASSP 2024 - 2024 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Visual Tracking Nonlinear Model Predictive Control Method for Autonomous Wind Turbine Inspection - Amer, Abdelhakim; Mehndiratta, Mohit; le Fevre Sejersen, Jonas; Pham, Huy Xuan; Kayacan, Erdal (2023 21st International Conference on Advanced Robotics (ICAR))

Analysis and Simulation of a Photonic Multiband FMCW Radar Sensor System using Nyquist Pulses - Kruse, Stephan; Schwabe, Tobias; Kneuper, Pascal; Kurz, Heiko G.; Meinecke, March-Michael; Scheytt, Christoph (German Microwave Conference (GeMiC))

Phase Noise Analysis of Photonic Radar Systems with Optical LO Distribution - Kruse, Stephan; Kneuper, Pascal; Schwabe, Tobias; Kurz, Heiko G.; Meinecke, Marc-Michael; Gonzalez-Huici, María A.; Scheytt, J. Christoph (nternational Conference on Microwaves for Intelligent Mobility (ICMIM))

Doppler Analysis of a Lidar-Photonic Radar Combined Sensor System - Kruse, Stephan; Brockmeier, Jan; Kneuper, Pascal; Schwabe, Tobias; Kurz, Heiko G.; Meinecke, Marc Michael; Scheytt, J. Christoph (International Radar Symposium (IRS))

Inverses Verfahren zur Identifikation piezoelektrischer Materialparameter unterstützt durch neuronale Netze - Koch, Kevin; Claes, Leander; Jurgelucks, Benjamin; Meihost, Lars; Henning, Bernd (Fortschritte der Akustik - DAGA 2024)

Einfluss der periodischen Struktur auf geführte Wellen in gewebeverstärkten Polymeren - Claes, Leander (Fortschritte der Akustik - DAGA 2024)

Beschreibung des akustischen Verhaltens verklebter plattenförmiger Strukturen mittels Kopplungsmodellen - Zeipert, Henning; Hölscher, Jonas; Claes, Leander; Henning, Bernd (Fortschritte der Akustik - DAGA 2024)

On the repulsion effect of coupled Lamb wave modes - Nicolai, Marcel; Bulling, Jannis; Lugovtsova, Yevgeniya; Zeipert, Henning; Prager, Jens; Henning, Bernd (Fortschritte der Akustik - DAGA 2024)

UNav-Sim: A Visually Realistic Underwater Robotics Simulator and Synthetic Data-Generation Framework - Amer, Abdelhakim; Álvarez-Tuñón, Olaya; Uğurlu, Halil İbrahim; Le Fevre Sejersen, Jonas; Brodskiy, Yury; Kayacan, Erdal (2023 21st International Conference on Advanced Robotics (ICAR))

Compact, High-Speed Mach-Zehnder Modulator with On-Chip Linear Drivers in Photonic BiCMOS Technology - Kress, Christian; Schwabe, Tobias; Rhee, Hanjo; Scheytt, J. Christoph (IEEE Access)

Randomised material parameter impedance dataset of piezoelectric rings - Koch, Kevin; Friesen, Olga; Claes, Leander

Randomised material parameter piezoelectric impedance dataset with structured electrodes - Koch, Kevin; Claes, Leander

Analysis of Inverter Operation Modes of an IGBT-Based ZCS LLC Converter for a 2 kW Automotive On-Board DC-DC - Urbaneck, Daniel; Wiegard, Jan; Schafmeister, Frank (PCIM Europe 2024; IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)

Study on Sample Geometries for Ferrite Characterisation in the MHz-Range - Piepenbrock, Till; Keuck, Lukas; Schachten, Sebastian; Böcker, Joachim; Schafmeister, Frank (PCIM Europe 2024; IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)

Pitfalls and their Avoidability in the Double-Pulse Test - Förster, Nikolas; Urbaneck, Daniel; Kohlhepp, Benedikt; Kübrich, Daniel; Schafmeister, Frank (PCIM Europe 2024; IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)

FEM Modelling of Dimensional-Resonant Inductors for LLC Converters in MHz Range - Piepenbrock, Till; Schafmeister, Frank; Böcker, Joachim (SPEEDAM 2024; 27th International Symposium on Power Electronics, Electrical Drives, Automation and Motion)

Experimentally Verified 22 kW, 30 kHz LLC Resonant Converter Design with new Control for a 1 MW Cascaded H-Bridge Converter - Unruh, Roland; Böcker, Joachim; Schafmeister, Frank (ECCE Europe 2024; IEEE Energy Conversion Congress & Exposition Europe)

Flexible operation and integration of high-temperature heat pumps using large temperature glides - Knorr, Lukas; Schlosser, Florian; Horstmann, Nils; Divkovic, Denis; Meschede, Henning (Applied Energy)

Dimensioning and Lifetime Prediction Model for a Hybrid, Hydrogen-Based Household PV Energy System Using Matlab/Simulink - Möller, Marius Claus; Krauter, Stefan (Solar)
This paper presents a model of an energy system for a private household extended by a lifetime prognosis. The energy system was designed for fully covering the year-round energy demand of a private household on the basis of electricity generated by a photovoltaic (PV) system, using a hybrid energy storage system consisting of a hydrogen unit and a lithium-ion battery. Hydrogen is produced with a Proton Exchange Membrane (PEM) electrolyser by PV surplus during the summer months and then stored in a hydrogen tank. Mainly during winter, in terms of lack of PV energy, the hydrogen is converted back into electricity and heat by a fuel cell. The model was created in Matlab/Simulink and is based on real input data. Heat demand was also taken into account and is covered by a heat pump. The simulation period is a full year to account for the seasonality of energy production and demand. Due to high initial costs, the longevity of such an energy system is of vital interest. Therefore, this model was extended by a lifetime prediction in order to optimize the dimensioning with the aim of lifetime extension of a hydrogen-based energy system. Lifetime influencing factors were identified on the basis of a literature review and were integrated in the model. An extensive parameter study was performed to evaluate different dimensionings regarding the energy balance and the lifetime of the three components, electrolyser, fuel cell and lithium-ion battery. The results demonstrate the benefits of a holistic modelling approach and enable a design optimization regarding the use of resources, lifetime and self-sufficiency of the system

Consistent Optical and Electrical Noise Figure - Noé, Reinhold (Journal of Lightwave Technology)

Mechatronik und elektrische Antriebe / Mechatronics and electrical drives - Böcker, Joachim

Nonlinear S-Parameter Behavioral Model of a Photonic Radar Transceiver Chipset for Automotive Applications - Kruse, Stephan; Schwabe, Tobias; Kneuper, Pascal; Meinecke, Marc-Michael; Kurz, Heiko G.; Scheytt, J. Christoph
This paper presents a method to model monolithically integrated photonic radar transceiver (TRX) with optical local oscillator (LO) distribution in silicon germanium (SiGe) electronic photonic integrated circuits (EPICs). The model proposed approximates the behavior of the nonlinear scattering (S)-parameters and noise figure of each building block of the TRX chipset by Laplace polynomials and hyperbolic tangent functions. The modular approach of the model allows to optimize hardware components with respect to the entire TRX system, and fault identification with reduced computational effort. The proposed method is validated using the first monolithically integrated photonic radar transceiver chipset and shows excellent agreement with the post layout simulation results and, including the photodiode (PD) bandwidth (BW) degradation, also with the measurements.

Numerical study of light backscattering from layers of absorbing irregular particles larger than the wavelength - Alhaddad, Samer; Förstner, Jens; Grynko, Yevgen (Journal of Quantitative Spectroscopy and Radiative Transfer)
Keywords: tet_topic_scattering

LoRa Transceiver for Load Monitoring and Control System in Microgrids - Mwammenywa, Ibrahim; Petrov, Dmitry; Holle, Philipp; Hilleringmann, Ulrich (2022 International Conference on Engineering and Emerging Technologies (ICEET))

Investigation of change in dispersive behaviour during adhesive curing in multi-layered structures - Zeipert, Henning; von Germeten, Christian; Friesen, Olga; Claes, Leander; Johannesmann, Sarah; Henning, Bernd (Fortschritte der Akustik - DAGA 2023)

Bestimmung der Volumenviskosität mittels akustischer Absorptionsmessung - Claes, Leander (Fortschritte der Akustik - DAGA 2023)

Characterization of adhesion strength using guided ultrasonic waves - Nicolai, Marcel; Zeipert, Henning; Lugovtsova, Yevgeniya; Bulling, Jannis; Johannesmann, Sarah; Prager, Jens; Henning, Bernd (Fortschritte der Akustik - DAGA 2023)

Phase-preserving methods to visualise ultrasonic fields with schlieren imaging - Hetkämper, Tim; Koch, Kevin; Claes, Leander; Henning, Bernd (tm - Technisches Messen)
Keywords: Schlierentechnik

Tailoring the directive nature of optical waveguide antennas - Farheen, Henna; Yan, Lok-Yee; Leuteritz, Till; Qiao, Siqi; Spreyer, Florian; Schlickriede, Christian; Quiring, Viktor; Eigner, Christof; Silberhorn, Christine; Zentgraf, Thomas; Linden, Stefan; Myroshnychenko, Viktor; et al. (Integrated Optics: Devices, Materials, and Technologies XXVII)
We demonstrate the numerical and experimental realization of optimized optical traveling-wave antennas made of low-loss dielectric materials. These antennas exhibit highly directive radiation patterns and our studies reveal that this nature comes from two dominant guided TE modes excited in the waveguide-like director of the antenna, in addition to the leaky modes. The optimized antennas possess a broadband nature and have a nearunity radiation efficiency at an operational wavelength of 780 nm. Compared to the previously studied plasmonic antennas for photon emission, our all-dielectric approach demonstrates a new class of highly directional, low-loss, and broadband optical antennas.
Keywords: tet_topic_opticalantenna

Optimized silicon antennas for optical phased arrays - Farheen, Henna; Strauch, Andreas; Scheytt, J. Christoph; Myroshnychenko, Viktor; Förstner, Jens (Integrated Optics: Devices, Materials, and Technologies XXVII)
We demonstrate a large-scale two dimensional silicon-based optical phased array (OPA) composed of nanoantennas with circular gratings that are balanced in power and aligned in phase, required for producing desired radiation patterns in the far-field. The OPAs are numerically optimized to have an upward efficiency of up to 90%, targeting radiation concentration mainly in the field of view. We envision that our OPAs have the ability of generating complex holographic images, rendering them an attractive candidate for a wide range of applications like LiDAR sensors, optical trapping, optogenetic stimulation and augmented-reality displays.
Keywords: tet_topic_opticalantenna

On Cryptography Effects on Interconnect Reliability - Ghazal, Abdulkarim; Sadeghi-Kohan, Somayeh; Reimer, Jan Dennis; Hellebrand, Sybille
Keywords: WORKSHOP

Time-Optimal Model Predictive Control of Permanent Magnet Synchronous Motors Considering Current and Torque Constraints - Brosch, Anian; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

How to suppress radiative losses in high-contrast integrated Bragg gratings - Hammer, Manfred; Farheen, Henna; Förstner, Jens (Journal of the Optical Society of America B)
High-contrast slab waveguide Bragg gratings with 1D periodicity are investigated. For specific oblique excitation by semi-guided waves at sufficiently high angles of incidence, the idealized structures do not exhibit any radiative losses, such that reflectance and transmittance for the single port mode add strictly up to one. We consider a series of symmetric, fully and partly etched finite gratings, for parameters found in integrated silicon photonics. These can act as spectral filters with a reasonably flattop response. Apodization can lead to more box shaped reflectance and transmittance spectra. Together with a narrowband Fabry–Perot filter, these configurations are characterized by reflection bands, or transmittance peaks, with widths that span three orders of magnitude.
Keywords: tet_topic_waveguide

A multi-mode super-fano mechanism for enhanced third harmonic generation in silicon metasurfaces - Hähnel, David; Golla, Christian; Albert, Maximilian; Zentgraf, Thomas; Myroshnychenko, Viktor; Förstner, Jens; Meier, Cedrik (Light: Science & Applications)
We present strong enhancement of third harmonic generation in an amorphous silicon metasurface consisting of elliptical nano resonators. We show that this enhancement originates from a new type of multi-mode Fano mechanism. These ‘Super-Fano’ resonances are investigated numerically in great detail using full-wave simulations. The theoretically predicted behavior of the metasurface is experimentally verified by linear and nonlinear transmission spectroscopy. Moreover, quantitative nonlinear measurements are performed, in which an absolute conversion efficiency as high as ηmax ≈ 2.8 × 10−7 a peak power intensity of 1.2 GW cm−2 is found. Compared to an unpatterned silicon film of the same thickness amplification factors of up to ~900 are demonstrated. Our results pave the way to exploiting a strong Fano-type multi-mode coupling in metasurfaces for high THG in potential applications.
Keywords: tet_topic_meta